Livelihood Vulnerability to Climate Change of Casava Smallholders in Central Highlands of Vietnam - Sen Lê; Hac Hien Nguyen (Forest and Society)
This study utilized the Livelihood Vulnerability Index (LVI) within the IPCC framework (LVI-IPCC) for cassava farming households in the central highlands of Vietnam. Data were gathered from a household survey (364 households) in Krong Bong and Ea Kar districts, Dak Lak province, in-depth interviews (22 key informants) and two focus group discussions. By analyzing variations in LVI components and conducting a Poisson regression analysis, the results revealed that cassava farming households in the studied areas exhibited moderate vulnerability to climate change and variability. Variations in vulnerability levels were observed between the two districts, with disparities found across sensitivity, exposure, and adaptive capacity. Differences in LVI were also evident between the Kinh and ethnic minority groups and between the poor and non-poor farming households, primarily attributable to variations in adaptive capacity. Key determinants of household livelihood vulnerability included the intensity of climate risks, the frequency of extreme climate events, market risks, environmental shocks, land slope, land area at risk of flooding, climate change knowledge, transportation means, market linkages, access to credit, and income diversification. The study further proposed strategies for local authorities and relevant agencies to enhance climate change resilience among cassava farming households.